Application of Plantaricin as an Antimicrobial Substrate in the Milking Process to Maintain Milk Quality in Smallholder Dairy Farm - Amalina Nur Wahyuningtyas; Irma Isnafia Arief; Epi Taufik (Indonesian Center for Animal Research and Development (ICARD), 2021)
Pathogenic bacterial contamination found in fresh cow's milk can be caused by poor milking management. This traditional milking process allows the milk to be contaminated from bacteria and dirt. Dyeing dairy cows using a commercial antiseptic is a common measure that can be done to prevent mastitis. Nipple immersion can be done after milking using synthetic antiseptic agents such as povidone iodine and chlorine. However, the use of synthetic antiseptics can actually cause a slight irritation and allergic effect and leave a residue. Therefore, it is hoped that the use of natural-based antiseptics can replace synthetic antiseptics. One of the natural based antiseptics that can be used is bacteriocin. This research aimed to analyze the application of the plantaricin IIA-1A5 as a substitute for synthetic antibacterial for teat dipping before milking namely microbiological tests, physicochemical tests, and pH measurements. The study was conducted using a randomized block design (RBD) with three replications. The treatment design consisted of control (without immersion), plantaricin 0.0074%, and povidone iodine 0.2%. Results showed application of plantaricin IIA-1A5 as teat dipping before milking can reduce the Total Plate Count, Escherichia coli, and Staphylococcus aureus population. The use of plantaricin IIA-1A5 as teat dipping did not change pH value and physicochemical quality (fat, SNF, lactose, and protein), which is below the Indonesian National Standard (SNI) about fresh milk. This ability is comparable to the iodine group, a synthetic antibacterial widely used by smallholder breeders in Indonesia. It is concluded that plantaricin IIA-1A5 can be used as a substitute for synthetic antibacterial (iodine group) for teat dipping before milking.